Learning Reductions that Really Work - Beygelzimer, Alina; Daumé III, Hal; Langford, John; Mineiro, Paul (arXiv:1502.02704, 2015)
We provide a summary of the mathematical and computational techniques that have enabled learning reductions to effectively address a wide class of problems, and show that this approach to solving machine learning problems can be broadly useful.